Design, Simulation and Control of a Marine Ship Model's Diesel Engine using Python and Matlab/Simulink - Kharroubi, Fouad; Fertat, Mohammed; El Hassani, Sanae; Ouahmane, Hassan (Manufacturing Technology Journal, 2021)
Marine ships engines are kind of huge diesel engines. In fact, the manner of controlling the speed of a ship can impact badly on the financial matters of the machinery operation. Thus, controlling the speed of the marine engines can avoid ships to face dangerous accidents. In purpose to prevent such kind of damages, marine systems simulator have been widely used as numerical tools. In fact, the simulation of speed control systems makes it possible to render the process of controlling the speed of an engine economical and eliminates many risks. In this article, we first present a mathematical formulation to illustrate the rotational velocity process of a ship model's marine diesel engine as well as its PID controller. Secondly, we introduce a novel python's marine simulator which includes a PID controller to govern marine ship model's engines and we compare its results with another PID diesel engine speed controller that we modelled, designed and simulated via Matlab/Simulink. Results of scenarios and experiences which we carried out have shown that the response of the speed control system when using python can be accurate and close to the one of Matlab/Simulink.
Keywords: Marine; Diesel Engine; Ship; Model; Simulation; Python; Matlab; Simulink; Towing Tank Testing; Speed-Control System